Facilitated lithium storage in hierarchical microsphere of Cu2S-MoS2 ultrathin nanosheets - Kadam, Sunil R.; Kalubarme, Ramchandra S.; Deshmukh, Shrutika P.; Panmand, Rajendra P.; Kawade, Ujjwala, V.; Kulkarni, Milind, V.; Deo, Shriniwas S.; Gosavi, Suresh W.; Kale, Bharat B. (ChemistrySelect, 2018)
Considering the high energy density Lithium ion batteries have become one of the best option for next-generation energystorage technologies. Transition metal chalcogenide nanomaterials are promising electrodes for Lithium-ion batteries. Molybdenum based layered chalcogenide materials wisely studied for rechargeable Li-ion batteries, due to its two-dimensional (2D) layered structure and better specific capacity. The three-dimensional (3D) synthesis of microsphere by ultrathin nanosheets is necessary for practical applications. Herein, the fabrication of a unique hierarchical 2D layered Cu2S-MoS2 nanostructure was (ultrathin nanosheets) demonstrated via in situ assembling of two-dimensional (2D) growths in facile solvothermal technique. The structural study reveals the existence of Cubic Cu2S and Rhombohedral MoS2 phase. Morphological study by FESEM and TEM shows unique ultrathin nanosheets of similar to 10 nm thickness self-assembled in the form of layered microsphere. In Li- ion storage testing, Cu2S-MoS2 electrode exhibited good specific discharge capacity of 651 mAhg(-1) at 50 mAg(-1) applied current and maintained 320 mAhg(-1) after 100 cycles. The facilitated advanced electrochemical performance attributed to layered ultrathin Cu2S-MoS2 composite nanosheets.